Clear, Calm, and Connected : Reflections on Church Leadership - Walters, Paul E.; Holley, Bob (Book collections on Project MUSE., 2020)
Clear, Calm, and Connected offers wisdom on leadership drawn from common ministry scenarios, family systems thinking, and Scripture. Paul E. Walters and Robert F. Holley, experienced pastors and long-time students of family systems theory, provide insights and tools to help ministry leaders--lay and ordained, as individuals and groups--view a congregation or organization and understand in fresh ways their own behavior, presence, and functioning. Through accessible stories about familiar ministry situations, readers are introduced to key elements of family systems theory: self-differentiation, cut-off, triangles, family projection, multi-generational transmission, emotional process in society, and the nuclear family emotional system. As readers grow in their understanding of these concepts, they will be able to serve congregations more effectively and conduct their personal life with more grace. Clear, Calm, and Connected is an excellent leadership training tool for boards, committees, or teams. Each chapter addresses one challenging issue, and chapters may be read in any order. Readers are encouraged to explore topics when anxiety is low, so when challenges arise and anxiety is higher, they have already practiced how to respond rather than react. It is an especially valuable resource for leaders working to discern mission, define roles, and respond to conflict.